Lipodystrophy in HIV patients: its challenges and management approaches - Singhania R (Dove Medical Press, 2011)
Rohit Singhania, Donald P KotlerDepartment of Medicine, St Luke's-Roosevelt Hospital Center, New York, NY, USAAbstract: HIV-associated lipodystrophy is a term used to describe a constellation of body composition (lipoatrophy and lipohypertrophy) and metabolic (dyslipidemia and insulin resistance) alterations that accompany highly active antiretroviral therapy. These changes, which resemble metabolic syndrome, have been associated with a variety of adverse outcomes including accelerated cardiovascular disease. The body composition and metabolic changes appear to cluster in HIV infection, although they are distinct alterations and do not necessarily coexist. Epidemiological studies have demonstrated multiple pathogenic influences associated with host, disease, and treatment-related factors. The adverse treatment effects were more prominent in early regimens; continued drug development has led to the application of metabolically safer regimens with equal or greater potency than the regimens being replaced. Disease-related factors include HIV infection as well as inflammation, immune activation, and immune depletion. The body composition changes promote anxiety and depression in patients and may affect treatment adherence. Treatment of dyslipidemia and alterations in glucose metabolism is the same as in non-HIV-infected individuals. Lipoatrophy is managed by strategic choice of antivirals or by antiviral switching, and in some cases by plastic/reconstructive surgery. Lipohypertrophy has been managed mainly by lifestyle modification, ie, a hypocaloric diet and increased exercise. A growth hormone releasing factor, which reduces central fat, has recently become available for clinical use.Keywords: lipoatrophy, lipohypertrophy, body composition, dyslipidemia, insulin resistance